The space : a guide for educators - Hare, Rebecca Louise; Dillon, Robert (Irvine, CA : EdTechTeam Press, 2016)
"Space is a beautifully designed book that respects that reading and learning can happen in a visually appealing way. Hare and Dillon walk educators through a series of questions and ideas on how learning spaces can support collaboration, creation, showcasing learning, and a learner's need for quiet. In addition to nudging thinking forward, Space provides practical design tips and uses images and testimonials for hacking learning spaces on a realistic budget. This book is designed to motivate, grow capacity, and energize educators to begin shifting their learning spaces to support modern learning for all students"
ARC
Hye Trade International
Keywords: Classrooms -- Planning; School facilities -- Planning; School decoration; Architecture